2015
DOI: 10.1371/journal.pone.0118262
|View full text |Cite
|
Sign up to set email alerts
|

OVCAR-3 Spheroid-Derived Cells Display Distinct Metabolic Profiles

Abstract: IntroductionRecently, multicellular spheroids were isolated from a well-established epithelial ovarian cancer cell line, OVCAR-3, and were propagated in vitro. These spheroid-derived cells displayed numerous hallmarks of cancer stem cells, which are chemo- and radioresistant cells thought to be a significant cause of cancer recurrence and resultant mortality. Gene set enrichment analysis of expression data from the OVCAR-3 cells and the spheroid-derived putative cancer stem cells identified several metabolic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 64 publications
2
28
0
Order By: Relevance
“…These subpopulations of cancer cells are believed to have CSC characteristics such as self-renewal ability and unlimited differentiation. Our group and other investigators have demonstrated that the spheroids of established ovarian cancer cell lines and transplanted human ovarian cancer possess the characteristics of OVCSLCs (3,4,(11)(12)(13)(14). In the present study, we also identified the characteristics of OVCSLCs in spheroids obtained from SKOV3 cells.…”
Section: Resultssupporting
confidence: 61%
“…These subpopulations of cancer cells are believed to have CSC characteristics such as self-renewal ability and unlimited differentiation. Our group and other investigators have demonstrated that the spheroids of established ovarian cancer cell lines and transplanted human ovarian cancer possess the characteristics of OVCSLCs (3,4,(11)(12)(13)(14). In the present study, we also identified the characteristics of OVCSLCs in spheroids obtained from SKOV3 cells.…”
Section: Resultssupporting
confidence: 61%
“…One of the experimental approaches for obtaining CSC-like properties in cells is to culture cancer cells in suspension, resulting in spheroid-shaped cells [68]. Indeed, a previous study has suggested that metabolic profiles in spheroid-derived cells from ovarian serous adenocarcinoma were different from those in cancer cells that were cultured in adherent plates [8].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a previous study has suggested that metabolic profiles in spheroid-derived cells from ovarian serous adenocarcinoma were different from those in cancer cells that were cultured in adherent plates [8]. The significance and implications of this difference were not fully discussed.…”
Section: Introductionmentioning
confidence: 99%
“…(Thus, no further normalization of measured analyte peak areas to indicators of cell number was necessary; normalization in all figures is only the result of post-processing and variable scaling.) Residues were derivatized as previously described 2224 . Briefly, 5 μL of 40 mg/mL O -methylhydroxylamine hydrochloride (MP Biomedicals, Santa Ana, CA) in pyridine was added to the dried sample and shaken at 1400 rpm for 90 min at 30°C.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Data analysis was performed as previously described 23, 24 . Briefly, instrument output was first analyzed with ChromaTOF (LECO, St. Joseph, MI) to determine baseline, peak area, and peak identities.…”
Section: Experimental Methodsmentioning
confidence: 99%